Locomotor and heart rate responses of floaters during small-sided games in elite soccer players: Effect of pitch size and inclusion of goalkeepers - Lacome, M.; Simpson, B. M.; Cholley, Y.; Buchheit, M. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To (1) compare the locomotor and heart rate responses between floaters and regular players during both small and large small-sided games (SSGs) and (2) examine whether the type of game (ie, game simulation [GS] vs possession game [PO]) affects the magnitude of the difference between floaters and regular players. Methods: Data were collected in 41 players belonging to an elite French football team during 3 consecutive seasons (2014-2017). A 5-Hz global positionning system was used to collect all training data, with the Athletic Data Innovation analyzer (v5.4.1.514) used to derive total distance (m), high-speed distance (>14.4 km/h, m), and external mechanical load (MechL, a.u.). All SSGs included exclusively 1 floater and were divided into 2 main categories, according to the participation of goalkeepers (GS) or not (PO) and then further divided into small and large (>100 m2per player) SSGs based on the area per player ratio. Results: Locomotor activity and MechL performed were likely-to-most likely lower (moderate to large magnitude) in floaters compared with regular players, whereas differences in heart rate responses were unclear to possibly higher (small) in floaters. The magnitude of the difference in locomotor activity and MechL between floaters and regular players was substantially greater during GS compared with PO. Conclusions: Compared with regular players, floaters present decreased external load (both locomotor and MechL) despite unclear to possibly slightly higher heart rate responses during SSGs. Moreover, the responses of floaters compared with regular players are not consistent across different sizes of SSGs, with greater differences during GS than PO.